INCREASE CUSTOMER AFFECTION: FOCUSING ON JUSTICE PERCEPTION EFFECT TO THE LOYALTY - Pramono, Aditya; Rahayu, Mintarti; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2021)
This research was aimed to determine the direct and indirect effect of justice perception, which would be analyzed in this research and based on three dimensions as distributive justice, interactional justice, and procedural justice to the customer affection and loyalty of patients in Xxx Hospital Malang. The research population covered the patients or families who have complained about service failure in the hospital. This data was based on the data from the public relation of Xxx Hospital Malang in 2018. The total sample was 232 respondents who had been selected through the saturated sampling method. The data was analyzed through the Partial Least Square PLS technique in SmartPLS 3.0 program application. The research finding indicated that distributive justice did not significantly affect customer affection from the three construct dimensions of justice perception. In contrast, the interactional justice and procedural justice affected positively and significantly the customer affection, and then the customer affection affected positively and significantly patient loyalty. This result showed that the higher interactional justice and procedural justice of patients would determine the higher customer affection of patients to Xxx Hospital Malang. The higher customer affection would determine the higher patient loyalty. For further research is recommended to re-explore the research variables that might affect the customer affection and loyalty directly on similar research objects or other hospitals, for instance, customer satisfaction, revisit intention, WOM, and other aspects. The next researches should also be done by developing the research model and using samples with different characteristics.Â